Your Macroeconomic Edge - Romero, Philip J (Business Expert Press, 2012)
Ebook from IG Library ; Businesspersons and investors have been conditioned to anticipate that after a period of turbulence following the "Great Recession," conditions will return to "normal." For the preceding generation (from 1982 to 2007), "normal" was the economic "Great Moderation": a period of low inflation and low unemployment that brought on high growth in asset values. Those days are gone. This book reviews the major, and largely inescapable, trends that will make the next generation a more challenging investment environment in all developed economies: an aging population and an overextended government. California today captures the challenges that will be faced by the American economy over the next decades. After summarizing these trends, the book outlines investing strategies for individuals and companies can use this new environment. It provides an extended case study in how greater economic literacy can offer readers an advantage for understanding the opportunities, and threats, presented by long- term trends.